Manajemen Kerja Operator MTs Anwaha - Nur Rizfa Adila; Syahrani; Nurhayati; Rahma Sarita; St. Norhalisa (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the work management of administrative operators and their role in managing educational data in Islamic junior high schools (madrasah tsanawiyah). The research employs a qualitative approach using a library research method, which involves reviewing various written sources such as books, scientific journals, and other relevant documents. The data used are secondary data collected through documentation techniques and analyzed using content analysis. Data validity is ensured through source triangulation. The results indicate that administrative operators play a crucial role as managers of educational data and information. Their responsibilities are not only technical but also reflect fundamental management functions, including planning, implementation, organization, supervision, and evaluation. The use of digital systems such as EMIS (Education Management Information System) and School Management Information Systems (SIMS) significantly enhances efficiency, accuracy, and accessibility of data management processes.However, several challenges are still encountered, including limited time, high workload, and unstable internet connectivity. These obstacles may affect the effectiveness of operators’ performance. Therefore, more effective management strategies are required, such as clear task distribution, improvement of facilities and infrastructure, and continuous technological training for operators. Consequently, administrative management in madrasah can be improved to become more effective, efficient, and reliable in supporting educational objectives Keywords: Operator work management, educational administration, EMIS, school management information system, Islamic junior high school Abstrak Penelitian ini bertujuan untuk menganalisis manajemen kerja operator administrasi serta perannya dalam pengelolaan data pendidikan di madrasah tsanawiyah. Penelitian menggunakan pendekatan kualitatif dengan jenis studi pustaka (library research), yang dilakukan melalui pengkajian berbagai sumber tertulis seperti buku, jurnal ilmiah, dan dokumen relevan lainnya. Data yang digunakan merupakan data sekunder yang dikumpulkan melalui teknik dokumentasi, kemudian dianalisis menggunakan metode analisis isi (content analysis). Keabsahan data dijaga melalui teknik triangulasi sumber.Hasil penelitian menunjukkan bahwa operator administrasi memiliki peran yang sangat penting sebagai pengelola data dan informasi pendidikan. Tugas operator tidak hanya bersifat teknis, tetapi juga mencerminkan fungsi manajemen yang meliputi perencanaan, pelaksanaan, pengorganisasian, serta pengawasan dan evaluasi data. Penggunaan sistem digital seperti EMIS dan Sistem Informasi Manajemen Sekolah (SIMS) terbukti mampu meningkatkan efisiensi, akurasi, dan kemudahan akses data.Namun demikian, masih terdapat beberapa kendala dalam pelaksanaan tugas operator, seperti keterbatasan waktu, beban kerja yang tinggi, serta kondisi jaringan internet yang kurang stabil. Kendala tersebut berpotensi memengaruhi efektivitas kinerja operator. Oleh karena itu, diperlukan strategi manajemen yang lebih optimal, seperti pembagian tugas yang jelas, peningkatan sarana prasarana, serta pelatihan teknologi. Dengan demikian, pengelolaan administrasi pendidikan di madrasah dapat berjalan lebih efektif, efisien, dan berkualitas Kata kunci: Manajemen kerja operator, administrasi pendidikan, EMIS, sistem informasi manajemen sekolah, madrasah tsanawiyah